2017
DOI: 10.4236/ojic.2017.74007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Rietveld Refinement and DFT Studies of Bis(4,5-dihydro-1<i>H</i>-benzo[g]indazole)silver(I) Hexafluorophosphate Complex Salt

Abstract: The new salt bis(4,5-dihydro-1H-benzo[g]indazole)silver(I) hexafluorophosphate, [Ag(N 2 H 10 C 11 ) 2 ]PF 6 , has been synthesized in methanol at ambient temperature and characterized by elemental and thermal analyses, FTIR and 1 HNMR spectroscopies, Rietveld refinement from powder diffraction data and DFT studies. The salt crystallizes in the triclinic space group P-1 with the parameters: a = 7.776 Å, b = 8.676 Å, c = 9.226 Å, α = 69.27˚ β = 89.86˚, γ = 74.50˚, V = 558.02 Å 3 , Z = 1. In the structure, the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This observed band, expected around 3300 cm −1 is shifted to lower wave number, due to the involvement of these protons in hydrogen bond formation with the oxygen atoms of the formate anion and that of water of crystallization. The weak multiple bands in the interval 2900 -2800 cm − [15]. Moreover, the sharp absorption obtained at 1600 cm −1 is due to C=O vibrations while the sharp multiple bands appearing in the interval 1497 and 1473 cm −1 correspond to the vibrations of C = C and C = N of the imidazole unit.…”
Section: Ir Spectrum Of [Zn(n2h8c5)2(ocho)2]•h2omentioning
confidence: 88%
“…This observed band, expected around 3300 cm −1 is shifted to lower wave number, due to the involvement of these protons in hydrogen bond formation with the oxygen atoms of the formate anion and that of water of crystallization. The weak multiple bands in the interval 2900 -2800 cm − [15]. Moreover, the sharp absorption obtained at 1600 cm −1 is due to C=O vibrations while the sharp multiple bands appearing in the interval 1497 and 1473 cm −1 correspond to the vibrations of C = C and C = N of the imidazole unit.…”
Section: Ir Spectrum Of [Zn(n2h8c5)2(ocho)2]•h2omentioning
confidence: 88%
“…1985) basis set were used. The hybrid B3LYP functional along with this basis set was applied to study of silver (I)-organic ligand complexes reported in the literature (Fomuta et al 2017;Altu ¨rk et al 2017). All calculations were performed using Gaussian 03 program package (Frisch et al 2004).…”
Section: Methodsmentioning
confidence: 99%